Thermal, mechanical and structural investigation of copolyimide-silica hybrids containing phosphine oxide - KARATAŞ, SEVİM (ELSEVIER SCIENCE SA, 2015)
In this study, a novel hybrid copolyimide was synthesized from copolyamic acid solutions (PAAs) obtained by the reaction between bis(3-aminophenoxy-4-phenyl)phenylphosphine oxide (m-BAPPO), 3,3'-diaminodiphenyl sulfone (DDS) and 3,3',4,4'-benzophenone tetracarboxylic dianhydride (BTDA), followed by thermal imidization. Hybrid materials containing 5% SiO2 were synthesized by sal-gel technique. The polyimide-silica hybrids were characterized by Fourier Transform Infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). Thermogravimetric analysis showed that the weight loss of hybrids is shifted to the higher temperature compared to the neat copolyimide. The contact angle measurements confirmed the hydrophobic surface of hybrids. Moreover, the gas permeability measurements were also done to take a step for forthcoming gas separation studies. The tensile modulus and strength of the copolyimides are good. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Flame retardance; Copolymers; Polyimides; Nanoparticles; SOL-GEL PROCESS; GAS SEPARATION; EPOXY-RESINS; MEMBRANES; PERMEABILITY; MORPHOLOGY; POLYMERS; COATINGS; AGENTS